Clinical efficacy and re-pregnancy outcomes of patients with previous cesarean scar pregnancy treated with either high-intensity focused ultrasound or uterine artery embolization before ultrasound-guided dilatation and curettage: a retrospective cohort study - Xi Wang; Bing Yang; Wenzhi Chen; JinYun Chen (BMC, 2023)
Abstract Background Cesarean scar pregnancy (CSP) treated with either high-intensity focused ultrasound ablation (HIFU-a) or uterine artery embolization (UAE) combined with ultrasound-guided dilation and curettage (USg-D&C) was effective. However, there is insufficient comparative research evidence on clinical efficacy and subsequent pregnancy outcomes after previous CSP treatment. This study aims to investigate the efficacy, safety, and subsequent pregnancy outcomes of HIFU-a compared to UAE before USg-D&C for the treatment of CSP. Methods Between January 2016 and July 2020, a total of 272 patients received the pretreatment with HIFU-a or UAE(HIFU-a group: n = 118; UAE group: n = 154). The clinical characteristics, treatment success rate, postoperative pregnancy rate and outcome of the two groups were compared and analyzed. Results The demographic characteristics of the two groups were similar. After pretreatment, the adverse events rate of HIFU-a group was lower than that of UAE group (10.40% (16/154) vs. 40.70% (48/118), P = 0.00). All patients received the USg-D&C. The HIFU-a group was of less intraoperative blood loss (10.00 (5.00-20.00) vs. 12.50 (5.00-30.00) ml, P = 0.03). There was no statistically significant difference between the two groups in success rates. However, the HIFU-a group was of a shorter duration of postoperative vaginal bleeding (12.00 (9.00-13.00) vs. 14.00 (12.00-15.00) days, P = 0.00). There was no significant difference between the two groups in terms of subsequent pregnancy rates (P = 0.317). However, the recurrent CSP (rCSP) rate in the HIFU-a group was lower than that in the UAE group (7.70% (6/78) vs. 19.70%(13/66), P = 0.03). Conclusions CSP treated with either HIFU-a or UAE combined with USg-D&C was safe and effective. Although no significant difference was found in the subsequent pregnancy outcomes of the two groups, the rCSP was more common in the UAE group. So, we recommend HIFU-a combined with USg-D&C treatment modality.